DOES KNOWLEDGE OF TECHNICAL LANGUAGE REQUIRE KNOWLEDGE OF STANDARD LANGUAGE? - Daniele, Franca (European Scientific Journal, ESJ, 2015)
The acquisition of a language necessarily requires some type of interaction with the surrounding environment. Language learning needs elements capable of stimulating new cerebral routes that in turn promote a better socio-biological adaptation and integration. The main role played by a special language is to transmit information that must overcome the educational, linguistic and even cultural barriers of the reader or listener. More frequently, worldwide, doctors are asked to communicate in the English language. All these issues are addressed in the present paper with the aim to clarify the concept of fluency development, and to show that acquisition of a technical language does not necessarily require fluency in the corresponding standard language. The notion that language development and acquisition is actually a sensitive-motor process has been highlighted. The main models attempting to assess acquisition of fluency in reading have been crossed. The analysis was limited to reading and comprehension skills in a technical language such as medical and scientific language because these latter skills can be more easily developed in university students, and these two skills are necessary for future doctors to have access to international scientific literature. Therefore, to further investigate on these issues, three different types of translations were submitted to post graduate medical students.